Explorations in applied geography - Chatterjee, Meera; Dutt, Ashok K.; Misra, H. N.; Singh, L. R. (Lekhraj R.) 1931- (New Delhi : Asoke K. Ghosh, Prentice-Hall of India, Private Limited, 2008)
Lekh Raj Singh, b. 1931, Indian geographer; contributed articles.
"Professor L.R. Singh felicitation volume."
Includes bibliographical references.
Keywords: Applied human geography -- India; Cultural geography -- India; Environmental geography -- India; Urbanization -- India